Topological analysis of the industrial product body (Al-Academy, 2024)
Topology is concerned with studying design structures through different dimensions, which allows the designer to control the behaviors of those structures. Therefore, the concept of dimensions is considered one of the basics of the composition of the industrial product and its attempt to control the material in the design. Therefore, directing these dimensions is one of the tools of engineering topology. Which expresses a basic concept in the study of surfaces by distinguishing between what is external and internal.Research problem:   What are the modern technical methods applied with topological characteristics in designing the body of an industrial product?Research goal: To reach the characteristics of topological formation techniques for the industrial product body.   The theoretical framework also included: identifying the nature of topology and the extent of its importance in the design system, what is the formal concept of the industrial product topology, and what are the most important techniques of topological design. The most important results and conclusions reached by the researcher were:   1-Flexibility is considered one of the most important characteristics of topological design within the dichotomy of stability and change, and then the characteristic of integration between the formal level and the functional level for shapes characterized by infinity, then comes the fluidity characteristic that takes into account the desire of the individual and changes with the change of time and place.2-The techniques varied according to the diversity of characteristics, so folds and twists became a form of topological techniques that the designer deals with. There are no regular shapes, no defined edges and flat surfaces.